Healthful Dietary Patterns and the Risk of Hypertension Among Women With a History of Gestational Diabetes Mellitus: A Prospective Cohort Study. Issue 6 (June 2016) - Li, Shanshan; Zhu, Yeyi; Chavarro, Jorge E.; Bao, Wei; Tobias, Deirdre K.; Ley, Sylvia H.; Forman, John P.; Liu, Aiyi; Mills, James; Bowers, Katherine; Strøm, Marin; Hansen, Susanne; et al.
Abstract : Women who developed gestational diabetes mellitus represent a high-risk population for hypertension later in life. The role of diet in the progression of hypertension among this susceptible population is unknown. We conducted a prospective cohort study of 3818 women with a history of gestational diabetes mellitus in the Nurses' Health Study II as part of the ongoing Diabetes & Women's Health Study. These women were followed-up from 1989 to 2011. Incident hypertension was identified through self-administered questionnaires that were validated previously by medical record review. Adherence scores for the alternative Healthy Eating Index 2010, the alternative Mediterranean diet, and the Dietary Approaches to Stop Hypertension were computed for each participant. Cox proportional hazard models were used to evaluate the associations between dietary scores and hypertension while adjusting for major risk factors for hypertension. We documented 1069 incident hypertension cases during a median of 18.5 years of follow-up. After adjustment for major risk factors for hypertension, including body mass index, alternative Healthy Eating Index 2010, alternative Mediterranean diet, and Dietary Approaches to Stop Hypertension scores were significantly inversely associated with the risk of hypertension; hazard ratio and 95% confidence interval comparing the extreme quartiles (highest versus lowest) were 0.76 (0.61–0.94; P for linear trend =0.03) for AHEI score, 0.72 (0.58–0.90; P for trend =0.01) for Dietary Approach to Stop Hypertension score, and 0.70 (0.56–0.88; P for trend =0.002) for alternative Mediterranean diet score. Adherence to a healthful dietary pattern was related to a lower subsequent risk of developing hypertension among women with a history of gestational diabetes mellitus. Abstract : Supplemental Digital Content is available in the text.